2014
DOI: 10.7589/2013-10-280
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR ASSESSMENT OFHEPATOZOON(APICOMPLEXA: ADELEORINA) INFECTIONS IN WILD CANIDS AND RODENTS FROM NORTH AFRICA, WITH IMPLICATIONS FOR TRANSMISSION DYNAMICS ACROSS TAXONOMIC GROUPS

Abstract: ABSTRACT:Parasites play a major role in ecosystems, and understanding of host-parasite interactions is important for predicting parasite transmission dynamics and epidemiology. However, there is still a lack of knowledge about the distribution, diversity, and impact of parasites in wildlife, especially from remote areas. Hepatozoon is a genus of apicomplexan parasites that is transmitted by ingestion of infected arthropod vectors. However, alternative modes of transmission have been identified such as trophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 67 publications
6
53
3
5
Order By: Relevance
“…Although the transmission of H. americanum has been experimentally confirmed by the ingestion of cysts containing -rodent tissues by dogs (Johnson et al, 2009), previous studies showed evidence that the Hepatozoon species found in free-living rodents in Brazil differ from those detected in domestic and wild canids (Maia et al, 2014;Demoner et al, 2016). Herein, the phylogenetic positioning and DNA divergence analysis reinforce the hypothesis that the transmission of Hepatozoon from preys (rodents) to canids is a rare event and may not contribute to the spread of the parasite among canids in Brazil (Maia et al, 2014;Demoner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the transmission of H. americanum has been experimentally confirmed by the ingestion of cysts containing -rodent tissues by dogs (Johnson et al, 2009), previous studies showed evidence that the Hepatozoon species found in free-living rodents in Brazil differ from those detected in domestic and wild canids (Maia et al, 2014;Demoner et al, 2016). Herein, the phylogenetic positioning and DNA divergence analysis reinforce the hypothesis that the transmission of Hepatozoon from preys (rodents) to canids is a rare event and may not contribute to the spread of the parasite among canids in Brazil (Maia et al, 2014;Demoner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of Hepatozoon spp. obtained from rodents and wild canids in South Africa showed to be phylogenetically related, suggesting a potential for transmission by predation of rodents by foxes (Vulpes pallida) (Maia et al, 2014). Additionally, Hepatozoon genotype sp.…”
Section: Introductionmentioning
confidence: 96%
“…adustus (side-striped jackal) (Maia et al, 2014a); similarly, one report in V. pallida (pale fox) in Senegal, (Maia et al, 2014a), one positive questing I. ricinus female in Luxembourg (Reye et al, 2010), and one report in a domestic dog with an unknown travel history in Ukraine (Hamel et al, 2013).…”
Section: A Better Understanding Of H Canis Vector Competence In Putamentioning
confidence: 91%
“…Therefore, knowing which Hepatozoon species are present has relevance for conservation of wild hosts and has veterinary implications in domestic animals. Additionally, molecular screenings have indicated that trophic pathways may explain the parasites found in both predators and prey, including rodent–snake (Tomé et al 2014 ) and rodent–canid (Maia et al 2014 ) food chains. At the same time, prevalence varies hugely between hosts and between study areas – for example Maia et al ( 2014 ) reported a prevalence of 36% versus 71% in two species of rodents ( Jaculus jaculus and Jaculus orientalis ) in North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, molecular screenings have indicated that trophic pathways may explain the parasites found in both predators and prey, including rodent–snake (Tomé et al 2014 ) and rodent–canid (Maia et al 2014 ) food chains. At the same time, prevalence varies hugely between hosts and between study areas – for example Maia et al ( 2014 ) reported a prevalence of 36% versus 71% in two species of rodents ( Jaculus jaculus and Jaculus orientalis ) in North Africa. It is clearly essential to screen more geographic regions for Hepatozoon prevalence, to improve estimates of diversity, to assess potential trophic pathways and to identify which genetic lineages can be found in diverse hosts.…”
Section: Introductionmentioning
confidence: 99%